The Purchasing Chessboard 64 Methods to Reduce Costs and Increase Value with Suppliers - Schuh, Christian; Raudabaugh, Joseph L.; Kromoser, Robert; Strohmer, Michael F.; Triplat, Alenka; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
The approach used on a given spend item should largely depend on the balance between supply power and demand power. That is the logic behind the bestselling Purchasing Chessboard®, used by hundreds of corporations worldwide to reduce costs and increase value with suppliers. The 64 squares in the Purchasing Chessboard provide a rich reservoir of methods that can be applied either individually or combined. And because many of these methods are not customarily used by procurement, the Purchasing Chessboard is also the perfect tool for helping buyers to think and act outside the box and find new solutions. This second edition of The Purchasing Chessboard addresses the new realities of a highly volatile economic environment and describes the many sometimes surprising ways in which the Purchasing Chessboard is being used in today's business world.
Procurement: the case for clout -- From four basic strategies to 64 methods -- Using the Purchasing Chessboard -- The Purchasing Chessboard -- The way forward.
Keywords: Economics; Industrial management; Industrial procurement; Economics/Management Science; Procurement; Management/Business for Professionals